Adaptive translation of medieval morality plays for contemporary African audiences: A case study of the morality play Everyman in Sesotho - Makutoane, T.J. (Acta Theologica, 2023)
Morality plays such as Everyman were first produced in England during the latter half of the 15th century. Their fictional nature, however, clothed moral truths in line with Catholic doctrines. The main aim of these plays was to teach audiences lessons in Christian living and salvation. Although these plays initially have a Catholic background, this does not exclude them from providing valuable lessons in Christian teaching to Protestant believers of the 21st century. The major problem with these plays is their interpretation of theological concepts such as “saints”, “Adonia”, and “priests”, making it difficult for Protestant believers, the Sesotho audience, in this case, to understand Everyman translated in Sesotho and written from a Catholic perception of such concepts. This article seeks to address the most important question: How can a better translation of the morality play Everyman be offered to Sesotho-speaking Protestant believers? The answer to this question is that an adaptative translation of the morality play Everyman into Sesotho better addresses the needs of these Protestant believers. In addition, this kind of translation should also be performative. The study uses the research methodologies of translation adaptation, performance criticism, and the functionalist skopos theory within the broader theoretical framework of a complexity approach to translation.